2020
DOI: 10.1101/2020.05.22.111005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potently neutralizing human antibodies that block SARS-CoV-2 receptor binding and protect animals

Abstract: The COVID-19 pandemic is a major threat to global health for which there are only 50 limited medical countermeasures, and we lack a thorough understanding of mechanisms of 51 humoral immunity 1,2 . From a panel of monoclonal antibodies (mAbs) targeting the spike 52 (S) glycoprotein isolated from the B cells of infected subjects, we identified several mAbs 53 that exhibited potent neutralizing activity with IC50 values as low as 0.9 or 15 ng/mL in 54 pseudovirus or wild-type (wt) SARS-CoV-2 neutralization tests… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 33 publications
3
73
0
4
Order By: Relevance
“…To examine the antibody response directed against SARS-CoV-2, we performed an indirect ELISA against the receptor binding domain (RBD) of the SARS-CoV-2 spike protein, a target of the neutralizing antibody response in both mice and humans [16,[45][46][47]. To quantify the anti-RBD antibody response, we compared the polyclonal sera from naïve Ifnar1 -/mice, to that of the SARS-CoV-2 infected Ifnar1 -/mice transfected with either the hACE2 or GFP mRNA ( Figure 2B).…”
Section: Adaptive Immune Response To Sars-cov-2mentioning
confidence: 99%
“…To examine the antibody response directed against SARS-CoV-2, we performed an indirect ELISA against the receptor binding domain (RBD) of the SARS-CoV-2 spike protein, a target of the neutralizing antibody response in both mice and humans [16,[45][46][47]. To quantify the anti-RBD antibody response, we compared the polyclonal sera from naïve Ifnar1 -/mice, to that of the SARS-CoV-2 infected Ifnar1 -/mice transfected with either the hACE2 or GFP mRNA ( Figure 2B).…”
Section: Adaptive Immune Response To Sars-cov-2mentioning
confidence: 99%
“…Recent studies have shown that related, potently neutralizing monoclonal antibodies that recognize the SARS-CoV-2 receptor binding domain (RBD) are often elicited in SARS-CoV-2 infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). These antibodies have great potential to be clinically impactful in the treatment and prevention of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…This likely accounts for the imperfect correlation between the titers of S-binding antibodies and viral neutralization activity across individuals (Robbiani et al, 2020). Due to its interaction with the host entry receptor (the angiotensin converting enzyme 2 -ACE2), the RBD of S represents the predominant target of vaccination and monoclonal antibody development strategies, and a growing number of antibodies against this domain have been described (Chi et al, 2020;Hansen et al, 2020;Robbiani et al, 2020;Zost et al, 2020). However, the RBD is one of the less conserved regions of the CoV proteome and antibodies against epitopes outside of the RBD have also been shown to have neutralizing activity (Chi et al, 2020;Poh et al, 2020): these may act in various ways, including by preventing important protease cleavage events and/or conformational changes required for successful entry into cells.…”
Section: Introductionmentioning
confidence: 99%